Supply in Marketing Process of Road Transport - Krizanova, Anna; Hrivnak, Martin (Communications - Scientific letters of the University of Zilina, 2005)
In defining the term marketing we can come out from the sole term, which means that the term marketing is necessarily connected with market activities. These activities are arranged in a particular sequence called a marketing process. Marketing process in road transport differs in many ways from the one in the manufacturing sphere, which is determined by the fact that a road enterprise provides services. This article deals both with the issue of marketing process in road transport and position of supply in this process.